Feminisme dan Teologinya: Interpretasi Hosea 4:6 di Era Postmodern - Wibowo, Darren Milano; Setyobekti, Andreas Budi (Pusat Studi Pentakosta Indonesia, 2024)
The postmodern era is an era where the world experiences many renewals, especially in various abstract matters. The changes that occur are dominated by the fields of art, culture, philosophy, and economics. In the changes that occur, there is actually a deconstruction and restructuring of the previous mindset. Feminism is a movement that is growing and undergoing rapid transformation in this postmodern era. In some ways, this movement is quite contrary to the Word of God. So that in the end it pollutes the true knowledge as written in Hosea 4:6. As a result, the church now has challenges from the feminist movement and its theology in this postmodern era. The research work entitled